Clinical and Pathological Features of Pheochromocytoma in the Horse: A Multi‐Center Retrospective Study of 37 Cases (2007–2014). (27th November 2015) - Luethy, D.; Habecker, P.; Murphy, B.; Nolen‐Walston, R.
Abstract : Background: Pheochromocytoma is the most common adrenal medullary neoplasm of domestic animals, but it is rare in horses. Antemortem diagnosis in horses is difficult, with clinical signs often being vague or non‐specific. Objective: The objective of this study was to describe the clinical, laboratory, and pathologic findings of pheochromocytoma in horses. Animals: Thirty‐seven horses diagnosed with pheochromocytoma based on postmortem examination from 2007 to 2014. Methods: Retrospective case series. Results: Pheochromocytoma was identified in 37/4094 horses during postmortem examination. Clinical signs consistent with pheochromocytoma had been observed antemortem in only 7 cases, with the remainder being incidental findings. Colic was the most common presenting complaint (13 of 37 cases) and tachycardia was noted in 95% of cases (median heart rate of 86 bpm in clinical cases). Hyperlactatemia (median, 4.9 mmol/L) and hyperglycemia (median, 184 mg/dL) were the most common clinicopathologic abnormalities. Hemoperitoneum caused by rupture of pheochromocytoma was noted in 4/7 clinical cases. Concurrent endocrine abnormalities (eg, thyroid adenoma, adrenal hyperplasia, pituitary pars intermedia hyperplasia or adenoma, parathyroid C‐cell carcinoma) were found in 27/37 horses, with 8/37 horses having lesions consistent with multiple endocrine neoplasia syndrome as described in humans. Conclusions: Pheochromocytoma was diagnosed in 0.95% of horses presented for necropsy. The majority of these were incidental findings, but pheochromocytoma was thought to contribute to clinical findings in 19% of cases, and multiple endocrine neoplasms were commonly seen. Usually an incidental finding at necropsy, pheochromocytoma may cause acute death from intraperitoneal exsanguination and should be considered in horses presenting with colic, tachycardia, and hemoperitoneum.